2004
DOI: 10.1111/j.1365-2672.2004.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of potentially pathogenic bacteria as free living and plankton associated in a marine coastal zone

Abstract: Aims: To determine the abundance of faecal and nonfaecal bacteria related to human and animal health, as free living or associated with small (>64 lm) and large (>200 lm) plankton, samples were collected monthly from the coastal zone at Messina (Italy). Methods and Results: Different enrichment and selective cultural methods were used to determine the abundance of bacteria in sea water and plankton. The bacteria were more frequently isolated from water and large plankton than from small plankton. Vibrio and Ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 25 publications
10
77
6
Order By: Relevance
“…Vibrio parahaemolyticus is less deadly, but causes a greater number of food-borne illnesses and can result in pandemic outbreaks of disease (Mead et al 1999, Strom and Paranjpye 2000, Wong et al 2000. Vibrio cholerae remains a major threat in many places around the globe as the causative agent of cholera, and its reservoir in the estuarine environment may play an important role in the survival and transport of pathogenic strains , Chakraborty et al 2000, Binsztein et al 2004 Previous studies have demonstrated strong relationships between Vibrio abundance and environmental conditions such as salinity, temperature, and attachment to planktonic organisms (Tamplin et al 1990, Heidelberg et al 2002, Lipp et al 2003, Louis et al 2003, Maugeri et al 2004. Harsh conditions, most often low temperature for Vibrio sp., stimulate a change in populations to a viable, but non-culturable (VBNC) state , Binsztein et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio parahaemolyticus is less deadly, but causes a greater number of food-borne illnesses and can result in pandemic outbreaks of disease (Mead et al 1999, Strom and Paranjpye 2000, Wong et al 2000. Vibrio cholerae remains a major threat in many places around the globe as the causative agent of cholera, and its reservoir in the estuarine environment may play an important role in the survival and transport of pathogenic strains , Chakraborty et al 2000, Binsztein et al 2004 Previous studies have demonstrated strong relationships between Vibrio abundance and environmental conditions such as salinity, temperature, and attachment to planktonic organisms (Tamplin et al 1990, Heidelberg et al 2002, Lipp et al 2003, Louis et al 2003, Maugeri et al 2004. Harsh conditions, most often low temperature for Vibrio sp., stimulate a change in populations to a viable, but non-culturable (VBNC) state , Binsztein et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] highlighted that the abundance of vibrios is often unrelated to that of faecal pollution indicators; therefore a complete assessment of the hygienic-sanitary quality of coastal waters should include these microorganisms to get a complete picture of the health risks associated to diseases from contaminated seafood. Halophilic vibrios are microorganisms autochthonous of marine environments; their abundance follows a seasonal trend, increasing during summer months [27]; moreover, coastal and estuarine habitats rich in organic polymers are typical habitats for vibrios whose growth depends on the availability of organic matter [11].…”
Section: Discussionmentioning
confidence: 99%
“…The enumeration of faecal coliforms is the first criterion to be satisfied to meet both environmental protection and human health. In addition, bacterial pathogens which are recognized as responsible for the outbreaks of intestinal diseases such as Vibrios, some of which are natural inhabitants of marine environments (Vibrio cholerae, V. parahaemoluticus) [11,12] require further attention, since these bacteria may constitute a potential health hazard, even if not under the above cited legislation [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arcobacter has been isolated from seawater and marine shellfish (see 1.3.2.5 and references therein), including A. butzleri that may be associated with plankton Maugeri et al, 2004). Other reports have identified all three human infectious species A. butzleri, A. cryaerophilus and A. skirrowii from seawater .…”
Section: Seawatersmentioning
confidence: 99%